The Foundations in the Development of Educational Materials for the Arabic Language for Non-Native Speakers/الأسس في تطوير المواد التعليمية للغة العربية لغير الناطقين بها - Dita Hanifah (Nurul Jadid University, 2018)
As well know together, teaching learning material improvement is one of the studying processes in acheaving certain educator target. This mean for creating an effective success teaching learning as the chose aim. Spiritual elements must be focused on Arabic language teaching material improvement. Because the students are creatures having sense of feeling. Like wikes, culture elements have an important role in developing teaching material in order that Arabic language can be accepted by the students. And futher Arabic language education graduate is as society's demand.كما لا يخفى علينا، أن تطوير المواد التعليمية هي أحد من عملية التعليمية للحصول على أفضل نتيجة ممكنة من حالة تعليمية معينة، فهو يهدف إلى جعل التعليم ذو فعالية، بمعنى النجاح في الوصول إلى المؤمل إنجازه، وفعال بمعنى الاستخدام الأمثل للموارد المتاحة والزمن.وارتبطت الأسس النفسية بالمواد التعليمية للغة العربية لكون الطفل كخلق ذي شعور وعاطفة. وللثقافة قيم خالدة ونتائج قيمة ولها دور هام في تطوير المواد التعليمية للغة العربية، ذلك كي تقرب اللغة العربية من نفوس الطلبة ويستجيبون بمتطلبات المجتمع الذي يعيشونها فيما بعد.